A novel missense mutation of CRYBB1 causes congenital cataract in a Chinese family. Issue 3 (May 2021) - Ji, Yanan; Zhao, Xiangyu; Zhang, Juanmei; Zhang, Dan; Tian, Chunliu; Zhang, Linlin; Zhao, Youcai; Zhao, Jun
Objective of the study: To identify the pathogenic gene and mutation site of a Chinese family with congenital cataract. Methods: Eight family members and 100 controls were employed, and targeted exome sequencing was used to identify the genetically pathogenic factor of the proband. Results: Targeted next-generation sequencing identified a novel missense mutation c.209A>C (p.Q70P) of CRYBB1 gene in the family. Sanger sequencing results showed that this heterozygous mutation was a causative mutation, which was not found in unaffected family members and healthy controls. Bioinformatics predicts that the effect of this mutation on protein function is probably harmful. Conclusion: We demonstrate that c.209A>C of CRYBB1 gene is a pathogenic mutation in the family of congenital nuclear cataract in this study. This is the first report that this mutation leads to congenital nuclear cataract, which broadens the mutation spectrum of CRYBB1 gene in congenital nuclear cataract.